Innovative Low-Cost Carbon/ZnO Hybrid Materials with Enhanced Photocatalytic Activity towards Organic Pollutant Dyes’ Removal - Pascariu, Petronela (Nanomaterials (Basel), 2020)
A new type of material based on carbon/ZnO nanostructures that possesses both adsorption and photocatalytic properties was obtained in three stages: cellulose acetate butyrate (CAB) microfiber mats prepared by the electrospinning method, ZnO nanostructures growth by dipping and hydrothermal methods, and finally thermal calcination at 600 °C in N(2) for 30 min. X-ray diffraction (XRD) confirmed the structural characteristics. It was found that ZnO possesses a hexagonal wurtzite crystalline structure. The ZnO nanocrystals with star-like and nanorod shapes were evidenced by scanning electron microscopy (SEM) measurements. A significant decrease in E(g) value was found for carbon/ZnO hybrid materials (2.51 eV) as compared to ZnO nanostructures (3.21 eV). The photocatalytic activity was evaluated by studying the degradation of three dyes, Methylene Blue (MB), Rhodamine B (RhB) and Congo Red (CR) under visible-light irradiation. Therefore, the maximum color removal efficiency (both adsorption and photocatalytic processes) was: 97.97% of MB (C(0) = 10 mg/L), 98.34% of RhB (C(0) = 5 mg/L), and 91.93% of CR (C(0) = 10 mg/L). Moreover, the value of the rate constant (k) was found to be 0.29 × 10(−2) min(−1). The novelty of this study relies on obtaining new photocatalysts based on carbon/ZnO using cheap and accessible raw materials, and low-cost preparation techniques.